2022
DOI: 10.1097/hmr.0000000000000355
|View full text |Cite
|
Sign up to set email alerts
|

Relationships and resilience at work and at home

Abstract: BackgroundThe COVID-19 pandemic has been an unusually comprehensive crisis that has taken a toll on people in their roles both at work and at home, giving rise to a new normal.PurposeRelational coordination theory shows how communicating and relating for the purpose of task integration drives positive outcomes for workers, their clients, and their employers. The ecological theory of work–family spillover shows how relational dynamics from work spillover into family life, and vice versa. We build upon these two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Weak RC has significant implications for workforce stability and efficiency, impacting job satisfaction, burnout, and turnover rates [31]. Poor RC can lead to increased stress and decreased intention to stay among healthcare professionals, contributing to a destabilized workforce.…”
Section: Relational Coordination's Role In Healthcare Effectiveness A...mentioning
confidence: 99%
“…Weak RC has significant implications for workforce stability and efficiency, impacting job satisfaction, burnout, and turnover rates [31]. Poor RC can lead to increased stress and decreased intention to stay among healthcare professionals, contributing to a destabilized workforce.…”
Section: Relational Coordination's Role In Healthcare Effectiveness A...mentioning
confidence: 99%
“…Professional burnout is a major factor influencing workforce productivity, and its prevalence increased during the COVID-19 pandemic due to reduced psychological security among employees. Moreover, remote work can have an adverse effect on WLB, as it contributes to job burnout (Ali, Gittell, Deng, Weger, and Dillon, (2023). Whiteoak, Abell, and Becker, (2023) indicated that the risk of job burnout is reduced when WLB is higher.…”
Section: H1: Hybrid Work Is the Main Tool Of Achieving Wlbmentioning
confidence: 99%
“…It also contradicts the public’s belief that health care organizations are benevolent, caring places. As such, we need to build on the emerging body of evidence that compassion can be systematically designed into health care delivery (McClelland & Vogus, 2021), as can high-quality caring (e.g., Rathert et al, 2022) and task relationships (e.g., relational coordination; Ali et al, 2023) to the benefit of health care workers and their organizations. However, we need more evidence of how these practices and relationships (re)shape climate (especially toxic climates like instrumental climate) and outcomes.…”
mentioning
confidence: 99%